The health of Australian baby boomers - Kendig, H; O'Loughlin, K; Wells, Y; Humpel, N (My University, 2010)
The large baby boomer cohort is beginning to reach retirement age. This paper reviews recent Australian literature on baby boomers' health and health behaviours. Databases were searched for peer-reviewed literature and the Internet for online studies and reports. The boomers can expect an increased life span compared to those in later life now. Boomers' health behavioural risks include physical inactivity, low vegetable consumption, obesity and rising medical risk due to increasing prevalence of diabetes. Their health will impact on workforce participation and retirement timing. There is substantial scope for health improvement and consequent quality of life as boomers age. However, little is known about health decision-making, inequalities between social groups and health information sources. Future research can yield a better understanding of the health trajectories of baby boomers in order to plan for health and service needs for an ageing Australia.
Keywords: Health -- Nutrition; Health -- Obesity; Ageing; Health and wellbeing; Ageing; Health; Nutrition; Obesity; Health and wellbeing